Teorema matematika dalam perancangan desain - Baskoro Suryo Banindro (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2017)
World industry flourished and grown rapidly in all fields, as a piece of design, scattered in the discipline of interior design, graphic design, fashion design, product design, craft industry. But behind the glorious and legends in the design is not much known about the Chronicle and its struggle would be a mathematical theorem. Through this small scale study tries to analyze flashbacks oversize presence behind the creation of the design. With the approach of a mathematical theorem how do stories, it was created and in what form is present in the design?Keywords: mathematical theorems, applications in industrial design